Fundamentals of Entrepreneurship ENT300 Satay Kamek / Mohd Syafiie Hj Ahmad... [et.al] - Ahmad, Mohd Syafiie; Roslan, Mohd. Amirul Mutaqin; Zanal Abidin, Marina Zafiera; Oslen, Salfariyah (2012)
We named our business as "Satay Kamek" where we selling and supplying various type of satay and sauces. Our restaurant use different concept of service compared to other satay restaurant which make us really unique. The customer will be serviced using the same concept as Sushi restaurant, which are they will be charged by the colour of plate we serve on our rotating machine. The sauce we serve are free for the customer. We also collaborate with Majlis Agama Islam Sarawak (MAIS) to get our halal certificate. Our priority is to serve the best and delicious satay and sauce to our customer in term of quality and taste. Also not forgot the services our restaurant will give to customer. Our employee will be professionally train to serve their customers to the fullest satisfaction. We are divide into four main manager. First, general and administration manager that will do all the early stages of planning. Second, marketing manager who in charge in marketing strategy. Third, operation manager who in charge in operation planning and working duty. Lastly, financial manager that responsible to ensure the flow of money to be record correctly. We ventured this business because we want to be the first entrepreneur that sell satay and sauce using the sushi concept in term of service. Our business is long term because demand for satay will keep increasing as in Malaysia, every year will have a festival or celebration for instance, Hari Raya Aidilfitri, Chinese New Year, Birthday Celebration and many more. The fact that satay is a well known food in Malaysia and suitable for all ages make us ventured this type of business. Thus, we strongly believe that our business will success as we serve various type of sauce for our satay and our business will spread throughout the world.